UPAYA MENINGKATKAN HASIL BELAJAR MATEMATIKA MENGGUNAKAN MODEL COOPERATIVE LEARNING TIPE STAD PADA SISWA KELAS V SDN 02 KOTABARU KECAMATAN TANAH PINOH - Bahrudin Bahrudin; Dede Suratman; Yakobus Ason (JURNAL PENDIDIKAN DASAR, 2014)
The purpose of this research is to fix the learning proses by using the cooperative learning of Student Teams Achievement Division type (STAD) on subject mathematic in grade VB, Public Elementary School 02, Kotabaru, Tanah Pinoh Distric, Melawi Regency, with the research subject was 27 students. The research found that there was direct impact of the model type used over the student performance result, where it was found that the number of students passed the subject was 22 students or 81.48%. Student activity sheet shown that the number of active students has the score 31 or 77.77% was about 21 students, where its also connected with the teacher activity on the learning proses with the score 86.5 or 80.09%. Key words: Cooperative Learning by STAD Type, Result of Learning on the Subject Mathematic